Improvements in metacognition mediate the effect of metacognitive remediation therapy: A non‐randomized controlled study among individuals with first‐episode psychosis. Issue 6 (7th September 2021) - Pine, Jacob G.; Moe, Aubrey M.; Wastler, Heather M.; Breitborde, Nicholas J. K.
Abstract: Aim: Metacognitive remediation therapy (MCR) has been shown to help individuals with first‐episode psychosis experience improvements in cognition, social functioning, vocational/educational functioning and quality of life. The theoretical model underlying MCR has yet to be empirically validated. Methods: Seventy‐three individuals with first‐episode psychosis completed measures of metacognition and cognition at enrollment and after 6‐months of care at a specialized clinical program for individuals with first‐episode psychosis. Among this group, we compared changes in these variables between the 21 individuals who opted to participate in MCR and the 52 individuals who did not participate in MCR. Results: Improvements in metacognition were moderated by MCR treatment participation. Consistent with the MCR theoretical model of change, increases in metacognition mediated the relationship between treatment and longitudinal changes in cognition. Conclusions: Our findings suggest that the benefits of MCR on cognitive functioning may stem, in part, from the ability of MCR to produce improvements in metacognitive functioning.